О родстве ископаемых и современных таксонов рода Perca (Osteichthyes, Percidae) - Щербуха, А.Я. (Вестник зоологии, 1993)
Perea fluvialilis aucl. from the Pleistocene Eastern Europe (Likhvin) is identified with P. lepidosoma of the Miocene Western Siberia. Together with recent P. schrenkii of Balkhash lake they are assigned to the subgenus Dengizperca. Recent Euro-Asiatic and North-American perches are suggested to belong to the genus Perea s. str.